Freedom of religion in Malaysia: Debates on norms and politico - Legal issues - Abdul Hamed Shah, Dian Diana; Mohd Sani, Mohd Azizuddin (Southeast Asian Human Rights Studies Network (SEAHRN), 2011)
Malaysia takes great pride in being a melting pot of different cultures, races and religions, co-existing under the purportedly “moderate Islamic nation” model. Yet, populations remain divided along racial and religious lines. Race and religion are not only politically salient; they are also jealously guarded to protect inter-ethnic sensitivities. Nevertheless, the vibrant development of human rights awareness and advocacy introduced an additional element into the dynamics of pluralism in Malaysia. Human rights have become standard talking points even amongst those in the vanguard of cultural, political, and religious conservatism. In Malaysia, cases invoking the right to religious freedom in the past decade have garnered widespread attention and caused considerable public uproar in the Muslim-majority nation. They involve (though not limited to) apostasy, child conversions, and persecution against non-mainstream religious doctrines. These cases raise pertinent questions about the parameters of religious freedom for Muslims and non-Muslims alike, especially when pitted against particular religious rules, societal norms, as well as the bigger idea of collective social responsibility and national stability. This paper offers a critical insight into the fundamental right to religious freedom in Malaysia. It examines several controversial cases which tackle the essential question of whether the Malaysian conception and practice of religious freedom is consistent with international human rights standards and entrenched constitutional rights. This paper demonstrates that while religious freedom is constitutionally guaranteed in Malaysia, there are other significant political, legal, and social dimensions to its exercise. It is hoped that this piece will prompt further discourses in drawing an acceptable idea of religious freedom informed by universal views of human rights, whilst maintaining aspects of common cultural values.